2008
DOI: 10.1152/ajpcell.00097.2008
|View full text |Cite
|
Sign up to set email alerts
|

Active Rab11 and functional recycling endosome are required for E-cadherin trafficking and lumen formation during epithelial morphogenesis

Abstract: herin (E-cadherin) is a major determinant for the acquisition of epithelial cell polarity and for the maintenance of epithelial integrity. The compartments and trafficking components required to sort and transport Ecadherin to the basolateral cell surface remain to be fully defined. On the basis of previous data, we know that E-cadherin is trafficked via the recycling endosome (RE) in nonpolarized and newly polarized cells. Here we explore the role of the RE throughout epithelial morphogenesis in MDCK monolaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 44 publications
6
141
0
Order By: Relevance
“…29 Inactivation of Rab25 or the related Rab11a resulted in a multiple lumen phenotype in epithelial cysts, which is characterized by failure of lumen expansion and retention of podocalyxin in subapical vesicles. 29,33 Multiple lumen formation has been linked with defective CDC42-mediated orientation of the mitotic spindle. 23,24 Interestingly, in response to Grhl2 inactivation in IMCD-3 cells, we found no evidence of multiple lumen formation or misorientation of the mitotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“…29 Inactivation of Rab25 or the related Rab11a resulted in a multiple lumen phenotype in epithelial cysts, which is characterized by failure of lumen expansion and retention of podocalyxin in subapical vesicles. 29,33 Multiple lumen formation has been linked with defective CDC42-mediated orientation of the mitotic spindle. 23,24 Interestingly, in response to Grhl2 inactivation in IMCD-3 cells, we found no evidence of multiple lumen formation or misorientation of the mitotic spindle.…”
Section: Discussionmentioning
confidence: 99%
“…On endocytosis from the oligodendroglial plasma membrane, PLP strictly enters the LE/Lys compartment and is never observed in RE (Winterstein et al, 2008). In epithelial cells, it has been demonstrated that a subset of cargos transit through RE intermediates on their biosynthetic route from the Golgi to the cell surface (Ang et al, 2004;Cresawn et al, 2007;Desclozeaux et al, 2008;Farr et al, 2009). Interestingly, the basolateral transport of those cargos traversing RE depends on VAMP3 (Fields et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, E-cad is known to be transported through the recycling endosomes to the plasma membrane in both Drosophila and mammalian cells (Desclozeaux et al, 2008;Langevin et al, 2005;Lock and Stow, 2005). In internalized salivary gland cells that are beginning to undergo apical membrane growth and elongation, E-cad localized to the apical membrane and AJs, as well as to discrete puncta at the basolateral membrane with Aval (see Fig.…”
Section: Research Articlementioning
confidence: 99%